Cyclooxygenase-2 expression and its association with vascular endothelial growth factor, microvessel density and clinicopathologic characteristics of colorectal carcinoma (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to investigate the expression of cyclooxygenase type-2 (COX-2) and its association with angiogenesis and clinicopathologic characteristics of colorectal carcinoma (CRC). COX-2 expression was detected by means of immunohistochemistry in a series of human tissue samples with CRC (n = 120), dysplasia tissue closely adjacent to carcinomas (n = 40) and normal colorectal mucosa (n = 40), and their expressions association with vascular endothelial growth factor (VEGF), CD31-labeled micorvessel density(MVD) in CRC and other clinicopathologic characteristics were investigated. The expression of COX-2 in CRC tissues (78.3%) was obviously higher than that in adjacent tissue and normal mucosal tissue (p